Effect of transportation distance and lairage time on selected behaviors and carcass parameters in zebu cattle—a study using the animal focal sampling method - Silva, Welligton Conceição da; Gouveia Júnior, Amauri; Damasceno Neto, Manoel Soares; Sousa, Luciano Fernandes; Barbosa, Antônio Vinícius Correa; Bruno Rebelo da Silva, Éder; Santos, Maria Roseane Pereira dos; Lourenço-Júnior, José de Brito; Camargo Júnior, Raimundo Nonato Colares; Silva, André Guimarães Maciel E. (Frontiers in Veterinary Science, 2024)
The objective of this study was to evaluate the effect of the transport distance and lairage time on behavioral indicators of zebu beef cattle in the resting pen of a slaughterhouse, using the focal animal technique. Eight lots of male zebu cattle, Nelore, aged approximately four years old, weighing on average 500±28.5 kg-1, from different municipalities, transported by land, were evaluated. The lots were grouped into two categories: short distance (> 500 km) and long distance (> 500 km). Five focal animals per evaluated lot were used in each cycle of behavior observation, randomly chosen and visually identified. The animal focal sampling method was used, with instantaneous recording, every five minutes per animal/hour. A video camera was used, placed at a fixed point in the corral. After slaughtering, bruises and carcass pH were evaluated. The respiratory rate (RR) was measured in two moments, 30 minutes after unloading (RR_I) and one hour before slaughter (RR_F), behavioral data were divided into four lairage periods (1 st , 2 nd , 3 rd and 4 th ), equally, and evaluated as repeated measures over time. The lairage time lowered the behaviors of headbutting (NCHBs), pushing (PsH), mounting (MT) and chasing away (CA), (p = 0.0001), these behaviors were more evident in animals transported for short distances, in the initial resting times, decreasing as they remained in the resting pen. There was effect of distance on the initial and final pH of the carcass, being greater in the short distance (p = 0.047). There was no effect of distance or lairage time on initial or final RR (p>0.05). In addition, animals transported over long distances showed less carcass injuries, observed during post mortem inspection. It is concluded that animals transported over short distances present a greater number of agonistic behaviors, such as NCHBs, MT, PsH and CA, predisposing to higher rates of bruising during lairage and more accentuated changes in the final pH of the meat.